Africa?s Quest for Modernity Lessons from Japan and China - Adem, Seifudein (London Springer, 2023)
This monograph addresses the complexity of China-Africa and Japan-Africa relations from a comparative perspective. The volume is divided into five sections. Section I focuses on the divergent perspectives that are reflected in the discourse on China-Africa relations. Section II discusses Japan?s economic modernization and its potential lessons for Africa. Section III compares the foreign policies of Japan and China in Africa and analyzes their supposed rivalries on the continent. Section IV explores the relationship between Southeast Asia and China and its relevance to Africa-China relations. Section V provides an in-depth case study of Ethiopia-China relations over the last century.
Includes index
Keywords: Africa